Tissue Engineering: From Basic Sciences to Clinical Perspectives - Aramwit, Pornanong; Motta, Antonella; Kundu, Subhas C. (BioMed research international, 2017)
[Excerpt] Tissue engineering and regenerative medicine are interre-lated terms and go hand in hand whether we discuss aboutcells (of any kind especially stem and progenitor cells), bio-materials as matrices (2D films, 3D forms of scaffolds,nanofibers, hydrogels, nanoparticles, aerogel, microcapsules,mats, biogel for 3D printing, blends of naturals and/or syn-thetics, and others), and addition of bioactive molecules(delivery of growth hormones and drugs) for improvementand/or regeneration of tissues for biomedical applications (inrelation to cartilage, shin, bone, blood vessels, nerve conduits,cardiac, adipose, tissue expression, and others). Therefore,it includes basic principles of biological sciences, materialchemistry, and relevant engineering subjects. Finally formedical applications after proper clinical verifications of theappropriate films, scaffolds, devices, delivery systems, andother relevant products are needed. [...]